Nurses' communication of pharmacogenetic test results as part of discharge care. (March 2015) - Haga, Susanne B; Mills, Rachel
As pharmacogenetic (PGx) testing is becoming integrated into routine clinical procedures for admitted hospital patients, consideration is needed as to when test results will be communicated to patients and by whom. Given the implications of PGx test results for current and future care, we propose that if results are not promptly discussed with patients when testing is completed, results should be discussed with patients during discharge care when possible, included in the printed or electronic discharge summary and a copy of the results sent to their primary provider. Nurses play an important role in discharge planning and care by providing patients with the necessary information and support to transfer from the hospital setting to an outpatient setting or to return to home and work. To promote nurses' ability to fulfill the role of communicating PGx test results, revised curricula and interprofessional and clinical decision support are needed.